The book of Exodus : composition, reception, and interpretation - Dozeman, Thomas B.; Evans, Craig A. (Craig Alan), 1952-; Lohr, Joel N. (Supplements to Vetus Testamentum., 2014)
Drawing on the latest in Exodus scholarship, this volume offers twenty-four essays on a wide range of topics related to Exodus, written by leading experts in the field. Topics include its formation, reception, textual history and translation, themes, theologies, and place within Judaism and Christianity.